EXPRESSION OF THE CONCEPT IN THE LINGUISTIC LANDSCAPE OF THE WORLD - Erkinova, Marxobo; Mohammad Yasin, Yoldash (Евразийский журнал социальных наук, философии и культуры, 2025)
Language is an important tool in the formation and expression of human ideas about the world. The linguistic landscape of the world reflects a person's worldview, cultural values and experiences through language. One of the main units that make up this landscape is the concept, which serves to generalize certain concepts through language. This article analyses how the concept is expressed in the linguistic landscape of the world, its national and cultural characteristics, and its metaphorical means of expression.